Photoelectrical properties of graphene/doped GeSn vertical heterostructures. Issue 35 (2nd June 2020) - Lv, Yanhui; Li, Hui; Ó Coileáin, Cormac; Zhang, Duan; Heng, Chenglin; Chang, Ching-Ray; Hung, K.-M.; Cheng, Huang Hsiang; Wu, Han-Chun
Abstract : The photoelectrical properties of graphene integrated with doped GeSn have been investigated and a high performance broadband photodetection can be achieved by integration of graphene with n-type GeSn. Abstract : GeSn is a group IV alloy material with a narrow bandgap, making it favorable for applications in sensing and imaging. However, strong surface carrier recombination is a limiting factor. To overcome this, we investigate the broadband photoelectrical properties of graphene integrated with doped GeSn, from the visible to the near infrared. It is found that photo-generated carriers can be separated and transported with a higher efficiency by the introduction of the graphene layer. Considering two contrasting arrangements of graphene on p-type and n-type GeSn films, photocurrents were suppressed in graphene/p-type GeSn heterostructures but enhanced in graphene/n-type GeSn heterostructures when compared with control samples without graphene. Moreover, the enhancement (suppression) factor increases with excitation wavelength but decreases with laser power. An enhancement factor of 4 is achieved for an excitation wavelength of 1064 nm. Compared with previous studies, it is found that our graphene/n-type GeSn based photodetectors provide a much wider photodetection range, from 532 nm to 1832 nm, and maintain comparable responsivity. Our experimental findings highlight the importance of the induced bending profile on the charge separation and provides a way to design high performance broadband photodetectors.